THE LAW ENFORCEMENT BY THE INDONESIAN NATIONAL POLICE (POLRI) TO ADDRESS THE TRIGGERS OF SOCIAL CONFLICT DURING THE 2019 ELECTIONS IN BANDAR LAMPUNG - Jimmy Tana; Surya Nita (Transpublika Publisher, 2024)
To address the social conflict triggers during the 2019 elections in Bandar Lampung, it is necessary to implement effective law enforcement. Simply relying on repressive penal measures is insufficient to deter potential perpetrators of election crimes, hoaxes, and hate speech. Likewise, preventive non-punitive approaches are unable to effectively curb the growth of social conflict triggers. Political actors take advantage of Bandar Lampung's history of social conflict, utilizing emotional manipulation as a primary tool in fueling conflicts. Therefore, the Bandar Lampung Police, through their law enforcement authority, must take action to prevent the escalation of these conflict triggers. This paper utilizes a descriptive qualitative approach to conduct research. It focuses on studying the optimization of law enforcement by the Police to minimize social conflicts during the 2019 Election. The research gathers primary data directly from respondents and secondary data from literature studies. The discovery reveals that enforcing the law to minimize social conflicts during the 2019 elections in Bandar Lampung is a challenging task for the police. Both repressive and preventive measures face difficulties. The enforcement of penal law lacks the necessary competence and resources, resulting in limited effectiveness in reducing social conflicts through criminal sanctions. On the preventive side, cooperation between institutions is lacking, polmas policies are not implemented properly, candidate socialization is not optimal, and the SPIS function is not maximized. As a result, hoaxes, hatespeech, and money politics easily spread, causing emotional distress among affected community groups.